Cardiac Damage Biomarkers and Heart Rate Variability Following a 118-Km Mountain Race: Relationship with Performance and Recovery - Ignacio Martínez-Navarro, Juan M. Sánchez-Gómez, Eladio J. Collado-Boira, Barbara Hernando, Nayara Panizo, Carlos Hernando (Journal of Sports Science and Medicine, 2019)
This study aimed to assess the release of cardiac damage biomarkers jointly with cardiac autonomic modulation after a mountain ultramarathon. Such knowledge and the possible relationship of these markers with race time is of primary interest to establish possible recommendations upon athletes’ recovery and return to training following these competitions. Forty six athletes enrolled in the Penyagolosa Trails CSP115 race (118 km and a total positive elevation of 5439 m) took part in the study. N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitive cardiac troponin T (hs-TNT) concentrations as well as linear and nonlinear heart rate variability (HRV) were evaluated before and after the race. NT-proBNP and hs-TNT significantly increased post-race; fifty percent of the finishers surpassed the Upper Reference Limit (URL) for hs-TNT while 87% exceeded the URL for NT-proBNP. Overall and vagally-mediated HRV were diminished and cardiac autonomic modulation became less complex and more predictable following the race. More pronounced vagal modulation decreases were associated with higher levels of postexertional NT-proBNP. Moreover, rise in hs-TNT and NT-proBNP was greater among faster runners, while pre-race overall and vagally-mediated HRV were correlated with finishing time. Participation in a 118-km ultratrail induces an acute release of cardiac damage biomarkers and a large alteration of cardiac autonomic modulation. Furthermore, faster runners were those who exhibited a greater rise in those cardiac damage biomarkers. In light of these findings, an appropriate recovery period after ultraendurance races appears prudent and particularly important among better performing athletes. At the same time, HRV analysis is shown as a promising tool to assess athletes’ readiness to perform at their maximum level in an ultraendurance race.